Control de las obligaciones tributarias para la Empresa TTT-Punto-Mas-Salud S.A.S. en Babahoyo en el periodo 2023. - Macias García, Kenny Leonardo (2025)
The study examines the control of tax obligations for TTT-PUNTO-MAS-SALUD S.A.S. in Babahoyo during 2023. It was found that the company has deficiencies in tax planning and management, leading to delays in paying taxes such as VAT, withholding taxes, and income tax, increasing the risk of penalties from the Ecuadorian Tax Authority (SRI). The research, using both quantitative and qualitative approaches, included interviews with the accounting department and document analysis. It was revealed that the lack of training among administrative staff contributes to tax declaration errors. As a result, strategies are proposed to optimize fiscal management, including the implementation of a tax control model and staff training. Key conclusions highlight the need to improve tax planning and meet deadlines to avoid financial penalties. Preventive measures, enhanced accounting management, and the use of technological tools are recommended to ensure regulatory compliance and the financial sustainability of the company.